Comparison of Oral Ondansetron and Metoclopramide in Reducing Postoperative Nausea and Vomiting in Gynecological Laparoscopic Procedures - Qadeer, Muhammad Kamil; Wadood, Roheena; Hameed, Jawad (Indus Journal of Bioscience Research, 2025)
Background: Postoperative vomiting and nausea frequently occur after gynecological laparoscopic surgeries, adversely affecting rehabilitation and patient satisfaction. Although metoclopramide and ondansetron are often utilized antiemetics, their relative efficacy in avoiding postoperative nausea and vomiting continues to be investigated. Objective: To compare the efficacy of oral ondansetron and metoclopramide in reducing postoperative nausea and vomiting in gynecology laparoscopic procedure. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from June 2024 to December 2024 at the Department of Obstetrics and Gynecology, Lady Reading Hospital, Peshawar. Methodology: A total of 194 female patients, aged 18 to 50 years, scheduled for gynaecological laparoscopic procedures, were assigned at random into two separate categories: Group A (ondansetron) & Group B (metoclopramide), having 97 patients in each group. Patients were administered either 4 mg of ondansetron with 8 mg of dexamethasone (Group A) or 10 mg of metoclopramide with 8 mg of dexamethasone (Group B) before surgery. The efficacy was assessed by the lack of vomiting and nausea within 24 hours following surgery. Results: The mean age of participants was 34.82±7.83 years for Group A and 35.75±8.69 years for Group B. The efficacy of ondansetron was significantly higher, with 55.7% of patients in Group A showing effectiveness, compared to 33% in Group B (p=0.001). Stratified analysis revealed that younger patients (≤40 years), married patients, and those with a BMI ≤25 showed a greater response to ondansetron. Conclusion: Ondansetron was found to be more effective than metoclopramide in preventing postoperative nausea and vomiting following gynecological laparoscopic surgery.